Trojan Pretenders: Dryden's The Last Parting of Hector and Andromache, Jacobitism, and Translatio Imperii. (March 2017) - Calvert, Ian
Abstract : Dryden's account of the infant Astyanax in his translation of the Hector and Andromache episode from Book 6 of the Iliad incorporates references to Virgil's Ascanius designed to celebrate the status of James Francis Edward Stuart (who was to become 'the Old Pretender') as the descendant of the two main branches of the Trojan royal family featured in Homeric and Virgilian epic. Dryden also celebrates James' matrilineal descent from Astyanax: James' mother, Mary of Modena, was a member of a royal house which claimed Astyanax as its founder. Dryden's translation draws on traditions concerning the post-Trojan fates of Ascanius and Astyanax to celebrate the birth of a royal heir whilst acknowledging the precariousness of that heir's future, which makes the poem available for Jacobite interpretations.